The Effect of Big Book Media on Beginning Reading Skills in 1st-Grade Students - Ramadhani, Anindita; Abdullah, Kusmajid; Handayani, Trisni (International Journal of Learning Reformation in Elementary Education, 2025)
This study aims to examine how Big Book media affects 1st-grade students' learning capacities. The method used is the Pretest-Posttest design for one experiment group, with one group serving as a sample for the study. An early reading skills test is provided before the need to use Big Book media to gather data. Analytical results indicate that there is a significant increase in reading comprehension after using the Big Book. Before the study, there were 3% of students who had not yet learned about huruf, 9% of students who had a specific need, and 16% of students who had learned about letters but had not yet been able to finish them. The average score for the pretest was 66.47, but the posttest score after using Big Book increased to 80.22, with a 6.5% increase. All of this indicates that Big Book media is an effective substitute for increasing students' reading comprehension and making a positive contribution to the learning process in elementary school. The implications of this study are the necessity of developing and implementing other educational media to increase students' understanding of the fundamentals of elementary school.